Primer in Genetics and Genomics, Article 1: DNA, Genes, and Chromosomes. (January 2017) - Dorman, Janice S.; Schmella, Mandy J.; Wesmiller, Susan W.
Precision medicine refers to the practice of determining a patient's unique genetic, biomarker, and other characteristics for the purpose of improving his or her clinical outcomes. Not all patients with the same clinical diagnosis respond equally to identical treatment regimens. By examining patients at the molecular level, health-care providers will be better able to apply the most effective therapies that each individual requires. To understand precision medicine, nurses must have a solid understanding of genomics and proteomics. The purpose of this article is to (1) provide a historical review of what and how we have learned about the genome, particularly in the past century, (2) explain the processes whereby genetic information in cellular DNA is transcribed to messenger RNA and translated to protein, and (3) introduce genetic and epigenetic mechanisms that regulate gene expression.